2019
DOI: 10.18488/journal.aefr.2019.91.52.63
|View full text |Cite
|
Sign up to set email alerts
|

Does Really Economic Freedom Matter for Growth in South Asia? Empirical Evidences from Pre-Economic Crises and Post-Economic Crises Period

Abstract: The discussion about the relationship between economic freedom and economic growth is not new and has always been extensively discussed in economic literature. But the question in this area is the consideration of the effects of global financial crises of 2008. This study attempts to answer the question: How does economic crises effect freedomgrowth nexus? This study analyses the relationship between economic freedom index (measured by Fraser Institute), individual components of economic freedom and GDP per ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These findings are in line with the study of Bjornskov et al (2010) and they argued that the societies with high income usually appreciate and endorse the decisions and values of judicial and democratic institutions without considering their material well-being. The coefficient of Sound Money is negatively significant in both lower-middle-income and middle-income countries which mean that citizens of countries value the access to sound money and these results are in line with Nadeem et al (2019) where they argued that monetary freedom has a negative impact on growth and social welfare in the cross country analysis. For the high-income countries, the coefficient is unexpectedly positively significant and the findings are in support of the argument that in high-income countries, citizens don't care about money growth or inflation (Gehring 2013).…”
Section: Resultssupporting
confidence: 72%
“…These findings are in line with the study of Bjornskov et al (2010) and they argued that the societies with high income usually appreciate and endorse the decisions and values of judicial and democratic institutions without considering their material well-being. The coefficient of Sound Money is negatively significant in both lower-middle-income and middle-income countries which mean that citizens of countries value the access to sound money and these results are in line with Nadeem et al (2019) where they argued that monetary freedom has a negative impact on growth and social welfare in the cross country analysis. For the high-income countries, the coefficient is unexpectedly positively significant and the findings are in support of the argument that in high-income countries, citizens don't care about money growth or inflation (Gehring 2013).…”
Section: Resultssupporting
confidence: 72%
“…Using the Heritage Foundation's index of economic freedom and applying the panel threshold approach,Gouider et al (2022) studied the relationship between economic freedom and growth for 35 emerging and developing countries from 1996 to 2018. They found evidence of a non -linear relationship and a differential threshold level of economic freedom in emerging and developing economies Nadeem, Yang, Akhtar, Dong, and Niazi (2019). found a positive association between economic freedom and growth in five South Asian countries from 1990 to 2015.…”
mentioning
confidence: 98%
“…Using a sample covering 160 countries, analyzed over 40 years, they discovered higher degrees of political instability and social polarization, but less democracy and central bank independence associated with more volatile inflation rates. Nadeem et al (2019) analyzed the relationship between economic freedom index (measured by the Fraser Institute), individual components of economic freedom, and GDP per capita growth of five South Asian countries over the period of 1990-2015. Their fixed effects regression results revealed that "GDP per capita growth is positively affected by economic freedom index and this relationship has weakened by the global economic crises of 2008" (Nadeem et al, 2019, p. 60).…”
mentioning
confidence: 99%